Analisis Tentang Konsep Pemasaran Jasa Dan Relationship Marketing - Sarwono - - (Innofarm:Jurnal Inovasi Pertanian, 2010)
Abstract : The dynamix of market economy has lead to a very tight competition. This tight competition forcecompanies to work extra hard to win the market. A good marketing, either for goods or services, basically requirebalancing the market force and marketing mix. As the market keeps changing, a shift in strategy stressing alsoneeded, particularly a shift from transactional marketing into relationship marketing.